Pengembangan Tes E-TKPN Berbasis Teknologi Cabang Olahraga Beladiri Perguruan Tapak Suci di SMK Muhammadyah 2 Palembang - Fatimah, Siti; Hartati, Hartati; Yusfi, Herri; Iyakrus, Iyakrus; Ramadhan, Arizky (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
The purpose of this research is to determine the development of technology-based E-Tkpn tests for the Tapak Suci College Martial Arts Sports Branch at SMK Muhammadyah 2 Palembang. This research uses the ADDIE development research method which begins at the Analysis, Design, Development (development), Implementation, and Evaluation stages. To develop a product in the form of a digital or application-based student fitness measurement test. This research produces a digital-based fitness test product for Indonesian students. The subjects of this research were vocational school students aged 15-17 years, totaling 30 students. This research was validated by 3 experts, the first being a sports test and measurement expert, namely Member of the South Sumatra KONI Sports Expert Council (94% in the very feasible category), an electrical media expert from the Sriwijaya University IT expert team (92% in the very feasible category) and a Linguist Expert by Secretary of the Language Education Department, FKIP, Sriwijaya University (88% very eligible category) used a questionnaire with various questions. From the three validations, there was an average of 91% of the e-TKPN application as a test medium for storing and processing test results that were suitable for use. However, from the results of statistical tests with a normality test of 0.088 > 0.05, a homogeneity test of Sig. 1,000 > 0.05 and the independent sample t-test is 1,000 > 0.05. The conclusion is that the development of an application-based Indonesian student fitness test is valid, practical, and effective. And can be used as a storage medium, managing student fitness test results both at school and in school extracurriculars. Keywords: Digital, e-TKPN, Indonesian Student Fitness